The Use of Mind Map in Collaborative Learning Activities of a Literary Reading Class - Suharto, Ririn Pratiwi; Rahayu, Eka Listianing; Agustina, Hiqma Nur (Universitas Nahdlatul Ulama Blitar, 2023)
The use of mind map as collaborative learning activities in literary reading class will be examined. The students will choose any kind of technology tools to make a mind map in reading class. The aims of this study are to identify the implementation of using mind map in collaborative learning activities of a literary reading class and students’ perceptions on it. This is a mixed method research. The data are taken from observation and questionnaires. The observation results are used to analyze the implementation of using mind map in collaborative learning activities of a literary reading class. The questionnaires are used to identify students’ perception on it. This study results that the students had positive perception toward the use of mind map and believed that it helps them learn the materials faster, save more time in doing collaborative work, understand the relationship between ideas, and more motivated to read literary texts.